Adherence to Rectal Mesalamine in Patients with Ulcerative Colitis. Issue 12 (December 2015) - Boyle, Marie; Ting, Amanda; Cury, Didia B.; Nanda, Kavinderjit; Cheifetz, Adam S.; Moss, Alan
Abstract : Background: Rectal mesalamine is an effective induction and maintenance therapy for ulcerative colitis. Little is known about the adherence rates to rectal mesalamine or barriers to its use. The aim was to quantify the prevalence of nonadherence to rectal mesalamine and to identify patient-reported barriers to adherence. Methods: A cohort of patients with ulcerative colitis was prospectively enrolled in this observational study and followed for 12 months. Adherence was assessed by tracking pharmacy refills (medication possession ratio). Individual interviews were undertaken in a subset of subjects. Transcripts from the focus groups and interviews were analyzed to identify themes and links between these themes using qualitative data software (MaxQDA). Results: Seventy patients prescribed rectal mesalamine were prospectively enrolled in the study. At enrollment, 39 of 70 subjects (55%) self-reported "occasional nonadherence" to rectal mesalamine. Over the 12-month follow-up period, only 20 subjects (26%) completed 3 or more refills. Males, or subjects prescribed a once-a-day suppository, were significantly more likely to refill than females (odds ratio = 3.3, 95% confidence interval, 1.1–10.9) or those prescribed suppositories more than once a day (odds ratio = 1.3, 95% confidence interval, 1.1–1.7). By medication possession ratio criteria, 71% of all subjects were nonadherent with their prescribed regimen (medication possession ratio <0.6). Nonadherers were significantly older than adherent subjects: mean age 48 years in nonadherers, versus 37 in adherers, P = 0.04. Patients who were nonadherent to rectal mesalamine frequently cited the mode of administration (65%) and busy lifestyle (40%) as reasons for nonadherence. Conclusions: Intentional nonadherence is common in patients who have been prescribed rectal mesalamine. Gender, age, frequency of dosing, and lifestyle factors may impact adherence. Abstract : Article first published online 6 August 2015.Supplemental Digital Content is Available in the Text.